Insuffisance rénale chronique au Centre Hospitalier Départemental Universitaire du Borgou (CHDU/B)à Parakou : profil étiologique et thérapeutique - DOVONOU, AC; VIGAN, J; AGBOTON, Bruno Leopold; HOUNSOUNOU, C; ZANNOU, DM; DJROLO, F (My University, 2011)
The aim of the study is to contribute to improving the management of chronic kidney disease (CKD) in CHDU / B, by identifying the etiological, and therapeutical profile of patients. A retrospective and descriptive study carried out in the Internal Medicine Service of the Departmental Hospital of Borgou, from January 1st, 2007 to December 31th 2009, from the medical records of patients. Were included in this study all patients in both (02) genders, up to sixteen (16) years older, in whom the diagnosis of CKD was made. All patients with acute renal failure (ARF) were excluded. The etiologies were dominated by nephroangiosclerosis (40.9%), followed by chronic glomerulonephritis (13.64%). Inhibitors Converting Enzyme (ACE) inhibitors were used in 90%. The rate of hemodialysis treatment was 2.3% for patients with end stage renal disease. Vascular nephropathy were the leading cause of chronic kidney desease in CHD / Borgou. It is essential to strengthen the staff by a nephrologist.
Keywords: Etiologies; chronic kidney disease; Parakou; Benin